Identifying the Components of a Model for Institutionalizing a Research Culture Among Teachers in Qeshm County - Fararian Sahli, Abdolbaset; Zakeri, Mokhtar; Nami, Kolsum (Iranian Journal of Educational Sociology, 2025)
Purpose: This study aims to identify the components of a model for institutionalizing a research culture among teachers in Qeshm County.Methods and Materials: The study employed a qualitative research design using a grounded theory approach. Participants included 20 educational managers and experts selected through purposive and snowball sampling methods. Semi-structured interviews were conducted to gather data, and the transcripts were analyzed using open, axial, and selective coding. The MaxQDA software was utilized for data organization and analysis, and theoretical saturation was achieved after the 18th interview.Findings: The analysis revealed six key dimensions essential for institutionalizing a research culture: enhancing research competencies, fostering psychological characteristics, motivating individual and professional engagement, addressing environmental and organizational factors, applying systemic strategies, and implementing supportive policy frameworks. Participants highlighted critical enablers, such as training programs, financial and organizational support, and leadership, as well as barriers, including insufficient funding, bureaucratic obstacles, and lack of institutional focus. Outcomes of a research culture were categorized as individual (e.g., increased self-efficacy), professional (e.g., enhanced teaching quality), and social (e.g., societal knowledge advancement).Conclusion: Institutionalizing a research culture among teachers requires a multifaceted approach that addresses personal, organizational, and systemic factors. The findings underscore the need for targeted training programs, organizational support, and policy interventions to overcome existing challenges and foster a sustainable culture of research among educators. These insights can guide educational leaders and policymakers in designing effective strategies to enhance research engagement in schools.